Buckling optimization of variable-stiffness composites with multiple cutouts considering manufacturing constraints. (December 2022) - Ding, Haoqing; Xu, Bin; Song, Liang; Li, Weibai; Huang, Xiaodong
Highlights: A novel CS-RBFs-based parameterized angle variable scheme. Buckling optimization of variable-stiffness composites with cutouts. Point-wise form of manufacturing constraints. P-norm function to obtain the global constraint value. A comparative study with the parametric level set method. Abstract: The progress of the automatic fiber placement (AFP) technique makes it viable to fabricate variable-stiffness (VS) composites with curvilinear fiber paths and promotes the rise of the VS composite design. However, traditional representation methods of fiber paths are not flexible for composites with cutouts and are also inconvenient to cooperate with the gradient-based solver. In this study, a parameterized angle variable scheme (PAVS) by the compactly supported radial basis functions (CS-RBFs) is proposed to represent the continuous fiber paths so that manufacturing constraints including minimal turning radius and gap/overlap can be conveniently related to the curl operation and divergence of the fiber angle vector field. A level set representation method of fiber paths is also provided for comparison. Two buckling optimization frameworks of the VS composite considering manufacturing constraints are then proposed based on these two representation methods. Numerical examples of two square plates with cutouts are conducted. Different numbers of support points, support radii, manufacturing constraints, and initial designs are investigated. Results indicate that the proposed PAVS needs few support points and a small support radius. It can also set initial design easily and describe the manufacturing constraints directly and quantitively.